Adults Experiencing Homelessness in the US–Mexico Border Region: A Photovoice Project - Moya, Eva Margarita; Chavez-Baray, Silvia M.; Loweree, Jacqueline; Mattera, Brian; Martinez, Nahomi (Frontiers in Public Health, 2017)
Homelessness is a social, economic, and political crisis in the United States. In particular, the U.S.-Mexico Border region has seen a surge of homelessness, specifically among veterans, women victims of intimate partner violence, and immigrants. In 2014, twelve persons in El Paso, Texas with experience of being homeless used the photovoice methodology to participate in a project titled, ‘The Voices and Images of the Residents of the Opportunity Center for the Homeless: A Visual Project on the Identity and Challenges Homeless Adults Face on the Border Region.’ The project was led by faculty from the Department of Social Work and facilitated by graduate students from the departments of social work, sociology and anthropology at the University of Texas at El Paso. In partnership with the Opportunity Center for the Homeless, a community based organization, a gallery of photographs with respective narratives was produced along with a video documentary. The participants identified four themes: broken systems, invisibility, opportunities and what works, and growth and determination. These themes represent participants’ life experiences with homelessness and their aspirations. In addition to the photo gallery, participants supported the development of a Call to Action asking the community, policy and decision makers to commit to changing the current social, economic, and political conditions affecting individuals experiencing homelessness. The gallery, Call to Action, and overall participant experiences with photovoice were shared during local, regional and national conferences and events, including three State of the Homeless Conferences led by the Opportunity Center for the Homeless in partnership with the university.